2016
DOI: 10.3389/fpls.2016.01188
|View full text |Cite
|
Sign up to set email alerts
|

QTL Detection and Elite Alleles Mining for Stigma Traits in Oryza sativa by Association Mapping

Abstract: Stigma traits are very important for hybrid seed production in Oryza sativa, which is a self-pollinated crop; however, the genetic mechanism controlling the traits is poorly understood. In this study, we investigated the phenotypic data of 227 accessions across 2 years and assessed their genotypic variation with 249 simple sequence repeat (SSR) markers. By combining phenotypic and genotypic data, a genome-wide association (GWA) map was generated. Large phenotypic variations in stigma length (STL), stigma brush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 80 publications
5
22
0
Order By: Relevance
“…3 ). This fact further confirmed that directional evolution for the allele size has occurred in rice [ 24 , 31 ]. We also observed that the SSR alleles tended to decrease in size from the low-latitude subpopulations (SP3 and SP4, 17–23゜N) to the high-latitude subpopulations (the other five subpopulations, 30–39゜N); this behaviour may be explained by the emergence of mutations or changes in the mutation rate causing a change in the allele size in rice [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…3 ). This fact further confirmed that directional evolution for the allele size has occurred in rice [ 24 , 31 ]. We also observed that the SSR alleles tended to decrease in size from the low-latitude subpopulations (SP3 and SP4, 17–23゜N) to the high-latitude subpopulations (the other five subpopulations, 30–39゜N); this behaviour may be explained by the emergence of mutations or changes in the mutation rate causing a change in the allele size in rice [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 73%
“…The second was the neighbour-joining method, which was carried out using MEGA version 5.0 based on Nei’s genetic distance [ 30 ]. The computations followed the same approach as those described in [ 31 ]. The coefficient of genetic differentiation ( F ST ) [ 32 ] was calculated to measure the fixation of different alleles in different subpopulations using Arlequin version 3.0 [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Association mapping (AM) based on linkage disequilibrium (LD) has been frequently used to search for more than two alleles at a gene locus or additional gene loci and explore the natural genomic diversity at a population level (Zhu et al, 2008 ; Brachi et al, 2011 ; Weigel, 2012 ). AM has been widely applied to exploit favorable marker alleles in rice for many traits, including yield traits (Garris et al, 2005 ; Agrama et al, 2007 ; Huang et al, 2010 , 2011 ; Zhao et al, 2011 ; Li et al, 2012 ; Vanniarajan et al, 2012 ; Dang et al, 2015 ; Yang et al, 2015 ; McCouch et al, 2016 ), quality traits (Borba et al, 2010 ; Huang et al, 2010 ; Jin et al, 2010 ; Feng et al, 2016 ), resistance traits (Famoso et al, 2011 ; Jia et al, 2012 , 2016 ; Cui et al, 2013 , seed vigor traits Cui et al, 2013 ; Dang et al, 2014 ; Rebolledo et al, 2015 ; Phung et al, 2016 ), and outcrossing traits (Yan et al, 2009 ; Huang et al, 2010 ; Dang et al, 2016 ). Although several studies on associations between markers and the PEL trait in rice have been reported (Begum et al, 2015 ; Crowell et al, 2016 ), no significant association has been detected between PEL and molecular markers.…”
Section: Introductionmentioning
confidence: 99%
“…The tested materials were 542 rice accessions 1 [46]; 121 of which were from Vietnam (Indica), while the remaining accessions were from China (Tej). These accessions range from 17°N to 54°N and 102°E to135°E, crossing 37°latitude from the north to the south and 33°longitude from the east to west (Additional file 6: Table S2).…”
Section: Plant Materialsmentioning
confidence: 99%